DEVELOPMENT OF BAITUSSHOLIHIN MOSQUE INFORMATION SYSTEM BASED ON ANDROID WITH THROW AWAY PROTOTYPING METHOD - Welia Desera Mandalika; Ali Ikhwan; Muhamad Alda (UPT Publication and Journal Management, Islamic University of Kalimantan, 2025)
The Baitussholihin Mosque information system is an Android-based application designed to store various types of data, including lecture videos, prayer schedules, and activity agendas, through the features and menus available in the app. This application helps mosque administrators store important data more effectively, reducing the risk of losing it. The research employs a qualitative research method, with data collection techniques including observation, interviews, and literature studies. The system development method used is the Throwaway Prototyping Method. The application that has been developed successfully organizes and provides important data reports based on the mosque's needs.